Multibeam bathymetry raw data (Kongsberg EM 122 working area dataset) of RV SONNE during cruise SO258/1 - Werner, Reinhard; Wölfl, Anne-Cathrin (PANGAEA, 2020)
Multibeam bathymetry raw data was recorded in the Indian Ocean during cruise SO258/1 that took place between 2017-06-07 and 2017-07-09. The data was collected using the ship's own Kongsberg EM 122. A sound velocity profiles (SVP) was applied on the data for calibration. SVP data are part of this dataset publication. This data is part of the DAM (German Marine Research Alliance) underway research data project and is shared in line with the FAIR principles.
Keywords: Multibeam Echosounder; Swath bathymetry